The US Economy, Global Imbalances and Recent Development: A Critical Review - Kalim Siddiqui (İstanbul İktisat Dergisi)
The United States has been running deficits on current accounts since the early 1990s. The current account deficits and surplus have caused dislocations in both developing and advanced economies. A recent study by Bullard et al. (2017) noted that the US economy is still the world’s largest economy and, according to the authors, between 2008-15 there was an average annual shortfall of 20% in fixed capital investment due to the 2008 crisis which also adversely impacted GDP growth and output (Bullard et al., 2017). This study will discuss the recent development in the US economy and also global imbalances in a historical perspective in order to try to understand the current situation. The discussion also includes the recent rise in China’s economy and the international trade. The study concludes that the trade deficits on the current scale cannot continue forever. Closing the trade deficit will require a more equal distribution of world spending, meaning a fall in US spending and a rise in spending from the rest of the world. Policy measures should be taken to increase state spending rather than rely on debt-fuelled private consumption to resolve inadequate aggregate demands. The reform should be made so as to seek profits in the real economy rather than ‘finance financing finance’. Finance should be made less globalised.